2009
DOI: 10.1021/ma902186e
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Diffusion in Self-Assembling Biodegradable Thermosensitive Hydrogels

Abstract: Hydrogel formation triggered by a change in temperature is an attractive mechanism for in situ gelling biomaterials for pharmaceutical applications such as the delivery of therapeutic proteins. In this study, hydrogels were prepared from ABA triblock polymers having thermosensitive poly(N-(2-hydroxypropyl) methacrylamide lactate) flanking A-blocks and hydrophilic poly(ethylene glycol) B-blocks. Polymers with fixed length A blocks (~22 kDA) but differing PEG-midblock lengths (2, 4 and 10 kDa) were synthesized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 44 publications
(100 reference statements)
4
52
0
Order By: Relevance
“…This evidence did not confirm the trend observed in nonphotopolymerized hydrogels, where polymers of shorter PEG length yielded a stronger hydrogel. 40 Hydrogels having shorter PEG length are expected to have higher G′ for two reasons. First, because at equal weight percentage of the polymer, the molar concentration of M 20 P 4 , having the smallest molecular weight, is higher as compared to the molar concentration of M 20 P 10 and M 20 P 20 .…”
Section: Resultsmentioning
confidence: 99%
“…This evidence did not confirm the trend observed in nonphotopolymerized hydrogels, where polymers of shorter PEG length yielded a stronger hydrogel. 40 Hydrogels having shorter PEG length are expected to have higher G′ for two reasons. First, because at equal weight percentage of the polymer, the molar concentration of M 20 P 4 , having the smallest molecular weight, is higher as compared to the molar concentration of M 20 P 10 and M 20 P 20 .…”
Section: Resultsmentioning
confidence: 99%
“…FITC-BSA and NR were chosen to stain hydrophilic and hydrophobic domains, respectively [21,33]. Subsequently 100 µl of each polymer mixture l of each polymer mixture was dispensed in duplo in a 96-well plate and incubated at 37 °C for 1h.…”
Section: Confocal Laser Scanning Microscopy (Clsm)mentioning
confidence: 99%
“…PEG end-capped with aliphatic blocks [32] and PEG flanked by pHPMAlac outer blocks [21,33], aqueous phase separation has been described in simple binary systems (one type of polymer in water), at certain conditions of polymer concentration and temperature. In this case, phase separation is attributed to the formation of polymer-rich regions composed of highly "packed" and interconnected polymeric clusters (flower-like micelles), and water-rich regions mainly composed of free micelles and hydrated single polymeric chains [34].…”
Section: Introductionmentioning
confidence: 99%
“…FRAP showed that the release rate of bovine serum albumin (BSA) depended on the protein size and the hydrogel molecular weight between the cross-links. In related work, FRAP was used to measure the diffusion of dextrans in the same type of hydrogel for different temperatures used during thermogelling (53). The diffusion and mobile fractions were found to decrease upon elevating the temperature above 25° C, and the mobility could be adjusted by changing the PEG block length.…”
Section: Diffusion Inside Hydrogelsmentioning
confidence: 99%